Tanggung Jawab Notaris terhadap Akta Otentik yang Dibuatnya Terkait Jangka Waktu Pensiun - I Gusti Ayu Ria Rahmawati; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2020)
An authentic deed is a letter whose form has been determined by law that can be used as perfect evidence made before a notary public. The notary concerned must take full responsibility in case of problems related to the deed he made, whether in Civil, Criminal, UUJN and Code of Ethics. The notary will be released from all of these responsibilities if he has retired from his position. This study aims to determine the responsibility of the notary for authentic deeds that are canceled in court and made after the retirement period. The research method used is normative law using a statutory approach and a conceptual approach. The results of the analysis show that the notary's responsibility for the authentic deed he makes when declared canceled in court can be divided into 4, namely a) civil liability, b) criminal responsibility, c) responsibility based on UUJN d) Responsibility based on the Code of Ethics. Then, the notary is still responsible even though the notary's term of office has ended or has retired. This can be carried out by the authorities as long as the authentic deed is null and void in existence at a grace period of 30 years from the date the deed is drawn up by the Notary. Through this research, it is hoped that the provisions regarding the responsibility of the notary public after retirement will be more defined regarding the maximum limit so as not to cause problems for both the notary and the party concerned